Sustainable Ecotourism Management In Para Village, Sangihe Islands Regency - Bataha, Katerina; Monintja, Donald K.; Pombengi, Jericho D (Publisher Cv. Inara, 2025)
This study aims to analyze the strategy of the Sangihe Islands Regency Tourism Office in managing Para Village as a community-based, sustainable ecotourism destination and to identify the challenges encountered in its management. The approach used is qualitative, using a case study method, with in-depth interviews, field observations, and documentation of local governments, Tourism Awareness Groups (Pokdarwis), and local communities. The study's results show that Kampung Para's ecotourism potential is enormous, with its main attractions being natural beauty, sustainable mangrove ecosystems, and the cultural richness of coastal communities. However, destination management still faces institutional and regulatory constraints, especially the unenacted Village Regulation (Perdes) on tourism levies, which has led to a weak legal basis and management accountability. Nevertheless, the community actively participates in maintaining the area's cleanliness, preserving local culture, and developing tourist attractions such as the Ampa Wayer dance and the Seke Maneke ceremony. The role of NGOs is significant in increasing community capacity through hospitality training, digital promotion, and policy assistance. To realize sustainable management, it is necessary to accelerate the legalization of Village Regulations, strengthen the Pokdarwis institution, and collaborate across sectors between the government, the community, and non-governmental partners. This research emphasizes that collaborative, locally rooted, value-based governance is the key to developing ecotourism that is inclusive, competitive, and supports achieving the Village SDGs, especially goals 8, 11, and 15.